If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/3(24-8c)=2(5c+1)
We move all terms to the left:
3/3(24-8c)-(2(5c+1))=0
Domain of the equation: 3(24-8c)!=0We add all the numbers together, and all the variables
c∈R
3/3(-8c+24)-(2(5c+1))=0
We multiply all the terms by the denominator
-((2(5c+1)))*3(-8c+24)+3=0
We calculate terms in parentheses: -((2(5c+1)))*3(-8c+24), so:We add all the numbers together, and all the variables
(2(5c+1)))*3(-8c+24
We add all the numbers together, and all the variables
-8c+(2(5c+1)))*3(+24
Back to the equation:
-(-8c+(2(5c+1)))*3(+24)
-(-8c+(2(5c+1)))*324+3=0
We move all terms containing c to the left, all other terms to the right
-(-8c+(2(5c+1)))*324=-3
| m-8=6=5m/3 | | 1+(4X(1+(6x(5+4))))=X | | 7x-12-9x=16-15x+13x-4 | | 15x+9=-2(x+6)-47 | | 4(2x+9)=12x+12-4x+24 | | 9x+22=2x+190 | | 7/3y=49 | | e+1.2=12 | | (e-1)*3=18 | | 3/4x1=13 | | 5(15x+50)=1,150 | | 10x-4=8x-8 | | a=70=2 | | 28x-9=7(4x+7) | | 4z-3+z+4=46 | | (x-2)^2/4+3/2=5/3 | | 16^3x+2=4.16^-2x+3 | | 14=-2c-14 | | 6x+2=2(3x-1) | | x-0.22=475.02 | | 1/8x-1/8=7/8 | | -8(x-2)+8=88 | | -3x+4=5x+2 | | 3p+7(-7+p)=16-3p | | 30×(0.5÷a)=20×(1.5÷a) | | 24=2y-14 | | x+7=4x+22 | | 4x-4+6x=5x-8+3x | | 24=2y+14 | | 17+7x=47+4x | | 4(q-2)+2=8q-6-2q | | 16+2n=6(7n-4) |